KEBIJAKAN BISNIS USAHA MIKRO KECIL DAN MENENGAH DALAM MENCAPAI KINERJA UNGGUL - Fatkhurahman, Fatkhurahman (Jurnal Ekonomi Bisnis Kompetif, 2024)
Business policies are guidelines or rules set by an organization to direct the operations, decision-making, and behavior of all members of the organization in achieving business goals. A good business policy is very important because it can provide structure, direction, and consistency in running a business. Micro, Small and Medium Enterprises (MSMEs) often face various issues related to business policies, which can affect the performance and sustainability of their businesses. Using descriptive research, data was collected from MSME managers and the results showed that the condition of the business policy of the small regional souvenir food industry in Riau Province was in the good enough category. This business policy variable obtained the largest dimension is hierarchical integration, while the smallest dimension is clarity of purpose. Keywords: Business Policy, MSME, Superior Performance